Students’ Perceptions of Role-Playing Games in Mathematics Learning: A Descriptive Study - Nurrosyadah, Naqiyyah; Susanti, Ely; Somakim (Jurnal VARIDIKA, 2026)
This study aims to describe students’ perceptions of the use of a role-playing game (RPG), Arithmetic Adventure: The Mystery of Polaria Village, in mathematics learning on arithmetic sequences and series. A quantitative descriptive research design was employed, involving 34 tenth-grade students at SMA Negeri 10 Palembang selected through purposive sampling based on their participation in RPG-based learning activities. Data were collected using a closed-ended Likert-scale questionnaire covering four aspects: motivation and engagement, perceived learning effectiveness, social interaction and collaboration, and challenges encountered during learning. Content validity was established through expert judgment, while instrument reliability was confirmed using Cronbach’s Alpha coefficients ranging from 0.77 to 0.91, indicating acceptable to excellent internal consistency. Descriptive analysis showed that students perceived the RPG positively in terms of motivation, engagement, and learning effectiveness, while challenges related to technical constraints and game complexity were reported at a moderate level. The integration of narrative-based gameplay with mathematical thinking stages—specializing, generalizing, conjecturing, and convincing—was perceived as supporting students’ reasoning and problem-solving processes. These findings suggest that RPG-based learning can serve as a meaningful and engaging instructional medium in mathematics, although its implementation requires careful design considerations and adequate technical support.